Nilai-nilai Cultural dalam Tabu - Sutrisno, Slamet (Jurnal Filsafat "WISDOM", 1991)
Culture encompasses a broad spectrum and its development shows certain shifts. Two main features of human are: value-systems and institutions which, especially in ancient societies, were both closely interconnected and intergrated.The connection between the value-aspect and instutional aspect in old societies is very obvious in taboo. The functions to taboo in traditional societies lay in their intergrative and stabilizing forces in society. The functioned also effective social controls.In traditional societies, taboo expressed at the same time a strong cosmic-religious awareness. Obedience of society members towards taboo showed deep reverence towards God and the harmony of all life in the universe.With the development society and the changes in culture, the quality of human life changed too, often taking place in revolutionary ways. Structural changes have their impact in value-system, resulting in changes of outlook in humankind, for whom these changes are basic demands.Because of all these changes, taboo as a cultural instution soon lost its significance; at role in society's life declined drastically. At the same time, humankind today is undergoing a crisis of meaning, which is also a value-crisis.This paper aim to purpose that audience rethinks and contemplates a new posibility of seacrhing for ways to reactualize values, like taboo, in today's lifethrough a set of transformations. Apart from cultural transformations the transformation of the society is in urgent need of revisioning.